Science Revived, or, The Vision of Alfred. A Poem in Eight Books - [Rev.] [Joseph] [Sympson] (Ptd. for J.A. Gameau, 1802)
Britain as a eutopia. Alfred calls upon the Goddess of Science to enlighten the world. She takes him, in the second book, to the Palace of Genius, where he sees thrones for Logic, Rhetoric, Geometry, Astronomy, History, Harmony, and Morality, with the last described as the fairest. The following books are a history of the rise of science and the arts after the low point of the fourteenth and fifteenth centuries. The final canto explains that science must be joined with liberty and then depicts the Britain of the time of writing as a eutopia.
Keywords: Male author